Contemporary German architecture in the context of selected philosophical literature - Serafin, Aleksander (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
Nowadays, philosophy clearly affects the architecture. Some of the patterns of thinking became the inspiration for designers and some others sanctioned certain ideas of the built architectural objects. The paper presents architectural expression of various trends that are evident in the literature that relates to aesthetics and philosophy at all. Both, concepts that refer to the continuity and tradition and the motives of complexity and difference are taken into discussion. The writings of Martin Heidegger seem to be a link between the two different notions.